VOLN27B: A New Head-Tailed Halovirus Isolated from an Underground Salt Crystal and Infecting Halorubrum. (14th December 2021) - Chen, Shaoxing; Dai, Yongpei; Liu, Jingwen; Zhang, Shimin; Chen, Feilong; Jin, Fanjie; Ruan, Peiyao; Li, Lu; Chen, Xiangdong
Abstract : A novel halovirus, VOLN27B, was isolated from a drill core sample taken at a depth of approximately 430 m, from a layer formed during the Cretaceous period (Anhui, China). VOLN27B infects the halophilic archaeon Halorubrum sp. LN27 and has a head-tailed morphotype with a contractile tail, typical of myoviruses. The average head diameter is 64 ± 2.0 nm, and uncontracted tails are 15 ± 1.0 × 65 ± 2.0 nm. The latent period is about 10 h. The maturing time of VOLN27B in cells of Halorubrum sp. LN27 was nearly 8 h. The adsorption time of VOLN27B on cells of Halorubrum sp. LN27 was less than 1 min. Virus particles are unstable at pH values less than 5 or when the NaCl concentration is below 12% (w / v ). VOLN27B and Halorubrum sp. LN27 were recovered from the same hypersaline environment and provide a new virus-host system in haloarchaea.